Donor hyperfine Stark shift and the role of central-cell corrections in tight-binding theory. (18th March 2015) - Usman, Muhammad; Rahman, Rajib; Salfi, Joe; Bocquel, Juanita; Voisin, Benoit; Rogge, Sven; Klimeck, Gerhard; Hollenberg, Lloyd L C
Abstract: Atomistic tight-binding (TB) simulations are performed to calculate the Stark shift of the hyperfine coupling for a single arsenic (As) donor in silicon (Si). The role of the central-cell correction is studied by implementing both the static and the non-static dielectric screenings of the donor potential, and by including the effect of the lattice strain close to the donor site. The dielectric screening of the donor potential tunes the value of the quadratic Stark shift parameter ( η 2 ) from −1.3 × 10 −3 µ m 2 V −2 for the static dielectric screening to −1.72 × 10 −3 µ m 2 V −2 for the non-static dielectric screening. The effect of lattice strain, implemented by a 3.2% change in the As–Si nearest-neighbour bond length, further shifts the value of η 2 to −1.87 × 10 −3 µ m 2 V −2, resulting in an excellent agreement of theory with the experimentally measured value of −1.9 ± 0.2 × 10 −3 µ m 2 V −2 . Based on our direct comparison of the calculations with the experiment, we conclude that the previously ignored non-static dielectric screening of the donor potential and the lattice strain significantly influence the donor wave function charge density and thereby leads to a better agreement with the available experimental data sets.